"Is This a Safe Space?": Examining an Emotionally Charged Eruption in Critical Language Pedagogy - Gordon Blaine West (MDPI AG, 2021)
Unexpected conflicts, or eruptions, in class during discussions of controversial issues are not uncommon in the field of English language teaching (ELT). This can be especially true for critical English language teachers who hope to address social justice issues in their classrooms. Existing literature of these events often mentions emotional responses of teachers and students, without fully analyzing the ways in which emotions are processed and constrained around these eruptions. This article examines a homophobic incident during an in-service English language teacher course taught by the author to illustrate ways in which emotions shaped the response to the incident, and how social justice aims can be achieved for critical language teachers in emotionally challenging environments, where there may be competing claims of injustice and narratives of oppression. Drawing on feminist theories of emotion, the case is made for a conceptualization of emotions not as private, individual experiences, but rather as public, socioculturally and materially mediated experiences. Social justice is theorized as an active fight against injustices that cannot be seen as an individual, isolated effort. Implications for critical language educators are shared.